Caenestheriella mariae sp. nov. (Crustacea: Branchiopoda: Spinicaudata: Cyzicidae): a new clam shrimp from Western Australia - Olesen, Jørgen; Timms, Brian (Zootaxa, 2005)
Caenestheriella mariae, a new species of the Spinicaudata (Branchiopoda), is described from Western Australia. It is most similar to the Australian Caenestheriella packardi (Brady, 1886), from which it differs most notably by several characters in the head region. In contrast to Caenestheriella packardi, Caenestheriella mariae sp. nov. (1) has a small hump anterior to the occipital condyle, (2) has a 90° pointed angle between the eye lobe and the rostrum, (3) has a more prominent eye lobe, and (4) lacks distinct sculpturing between the growth lines of the carapace. Caenestheriella mariae lives in gnamma (rock) pools when they hold water in winter-spring.